Diss rate rainwater 12C pH5.xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
The dissolution of IHE residues by dripping tests with rainwater stored at 12C. Leachate collected every 5 minutes and measured by HPLC.
Keywords: 'rainwater'; 'dripping test'; 'IHE residues'